Pengaruh Nilai dan Norma Terhadap Tradisi Ruwat Bumi di Desa Guci, Kabupaten Tegal, Jawa Tengah - Aminudin, Haekal; Kurnia, Heri; Apriliani, Afni (Academy of Social Science and Global Citizenship Journal, 2023)
Values ​​and Norms in the Ruwat Bumi Tradition in Guci Village, Tegal Regency, Central Java have a significant urgency for the process of social life. The values ​​and norms contained are basically a reflection of the teachings of the ancestors or ancestors which occurred due to the process of assimilation between Islam and Hinduism. This happens because there are cultures that interact with each other to produce existing systems of values ​​and norms. This tradition is a sacred tradition to preserve and protect what the earth has given to the local community, as well as respect for ancestors, religious ceremonies, giving offerings, slaughtering animals, sowing flowers, and celebrating the struggle for vegetables into a series of processes of the Ruwat Bumi Tradition carried out once a year to be precise in the month of assuyro. The method in writing scientific papers uses the descriptive literature method so that the data obtained is data sourced from scientific journals, books, and others that are relevant to the topic of writing. The results of writing this scientific work are basically the Ruwat Bumi Tradition in Guci Village, Tegal Regency, Central Java, which has a meaning that plays a role in maintaining the balance of life between the natural world and the supernatural world. Existing values ​​and norms are not far from what God has given for human survival. Respect for ancestors, diversity and tolerance, preservation of nature, religiosity, spiritualism, a sense of togetherness, respect and continuity are the basis for the formation of this culture. All of this cannot be separated from the role of the ancestors in responding to and appreciating what the earth has given them at that time. Ruwat Bumi in Guci Village is a symbol of togetherness, pride has a distinctive characteristic to make Guci Village rich in existing culture. The values ​​and norms contained in this ceremony should be able to be implemented and applied in social life so that a sense of unity and harmony between the nation and the state is created properly.